Translation and cultural adaptation of the US National Cancer Institute's patient-reported outcome (PRO) version of the CTCAE for Italian pediatric oncology populations. (August 2018) - Zucchetti, Giulia; Tirtei, Elisa; Bertorello, Nicoletta; De Luna, Elvira; Vallero, Stefano; Fagioli, Franca
Abstract: Purpose: This study intends to translate and make any necessary cultural adaptations of the Pediatric PRO-CTCAE version for Italian oncological patients aged 7–18 years and their caregivers. Methods: The questionnaire has been forward/backward translated into Italian and subjected to detailed verification by fluent Italian speakers, children and their parents, for use in clinical trials in Italian populations. The Italian version includes 130 questions that assess 62 symptoms. To verify the patients' comprehension some interviews were completed with 24 oncological children and adolescents in different age groups and 24 parents (Mage = 41.2). Caregivers were interviewed independently. Results: A final Italian version of the Pediatric PRO-CTCAE was produced. Across the age range, most patients and caregivers were able to understand and answer the questions. The 7–9 years old had greater challenges completing two terms which were retested in a second round of interviews. There were no comprehension differences on the basis of trials enrollment phase. Conclusions: The translation and adaptation of the Pediatric PRO-CTCAE confirms that this instrument is also suitable for assessing symptom toxicities among Italian cancer patients. Its rapid integration into care pathways is necessary to guarantee an early response to patient symptoms and to facilitate drug tolerability assessment. Highlights: First translation of a standardized method of adverse event reporting to enhance physician reporting. The incorporation of this tool into standard research data collection will permit to address threats to patients QoL and improve symptom control and supportive care. The incorporation of this tool will permit to sustain the role of "research nurse" in pediatric oncology.